Peran Badan Pertanahan Nasional dalam Penyelesaian Tumpang Tindih Penguasaan Kepemilikan Tanah di Kecamatan Bulango Utara, Desa Tuloa, Kabupaten Bone Bolango - Agustin Ali; Nirwan Junus; Nurul Fazri Elfikri (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2025)
Land conflicts, particularly overlapping claims of land ownership and control, represent a structural issue that continues to recur in Indonesia due to population growth, technological advancement, and the increasing complexity of development. This study aims to analyze the role of the National Land Agency (BPN) in resolving overlapping land ownership cases in Tuloa Village, North Bulango District, Bone Bolango Regency. The research employs an empirical legal approach, collecting data through interviews, field observations, and document analysis, including land regulations and BPN archives. The findings reveal that the primary causes of overlapping land claims are the lack of physical boundary maintenance and changes in ownership status due to inheritance. BPN plays a role in document verification, mediation, and handling complaints, although it faces challenges such as staff rotation and a weak documentation system. The resolution of land disputes in Tuloa Village was achieved through a familial approach involving deliberation, facilitated by the village government and BPN, resulting in a mutual agreement on land division. The implications of this study highlight the need to strengthen BPN’s institutional capacity, enhance public legal awareness on land issues, and improve the administrative system to prevent similar conflicts in the future.